Impact of three health educational strategies on breast self-examination knowledge, beliefs and practices among female public university students - Zavare, Mehrnoosh Akhtari (2013)
Breast cancer is the most common cancer and the second principal cause of cancer deaths among women world wide as well as in Malaysia. Early detection of breast cancer can play an important role in reducing cancer morbidity and mortality. Mammography and clinical breast examination (CBE) are considered as screening methods for early detection of breast cancer. Practicing breast self examination (BSE) could provide an opportunity for women to know how their breasts normally feel and notice any changes in their breast. Studies have shown that among younger women breast cancer tend to be more advanced stage and more aggressive than those affecting older women. The objective of this study was to comparing health educational strategies towards breast self examination practice among female public universities’ students in Klang Valley. A multi-stage random sampling was used for selection of participants. All female students those fulfill the inclusion criteria of the study were invited to participate in the study with informed consent form. A translated, reliable and valid tool adopted from Champion’s Health Belief Model was used to determine women’s perceptions on breast cancer and BSE. Three types of intervention strategies namely knowledge-based, knowledge-based and skill-based and skill-based strategies were implemented for this study. The strategies were supported by educational module, presentation, and demonstration on BSE practice on breast silicon model. The control group received all of the informational material and BSE practice after the completion of the study. To evaluate the effect of the intervention, data were collected at baseline, 6 months and 12 months after intervention in 3 intervention groups and control group. Descriptive and multivariate statistics were used for analysis the data using SPSS version 19.0. Baseline data were collected from 792 female students in four groups. At 12- month follow assessment, data was collected from 183 (92.42%) in intervention group one, 186 (93.93%) in intervention group two, 189 (95.45%) in intervention group three and 188 (94.94%) in control group. The mean age of participants was 22 ±1.20 years and majority of them were Malay (728, 91.9%), single (767, 96.8%). After intervention, there was a significant increase in the mean score of knowledge on breast cancer in intervention Group One (knowledge-based) (11.28-12.15, p<0.001), intervention Group Two (knowledge-based and skill-based strategy)(11.32-13.09, p<0.001) and intervention Group Three (skilled-based strategy)(11.05-11.52, p<0.008). Regarding knowledge of BSE, there was a significant increase in the mean score of knowledge BSE in intervention Group One (6.19-7.13, p<0.001),intervention Group Two (6.29-7.79, p<0.001) and intervention Group Three (6.01-6.70,p<0.001). Proportion of BSE practice was increased in intervention Group One (20.2%-21.9%, p<0.005), intervention Group Two (23.7%-30.1%, p<0.001) and intervention Group Three (18.0%- 24.3%, p<0.001), over the twelve months follow up in the intervention groups. Health Belief Model (HBM) constructs significantly differences for susceptibility, confidence and motivation in the intervention groups and control group (p<0.05).the logistic regression model showed that change in total knowledge score of breast cancer (OR=1.58), motivation (OR=1.47), susceptibility to breast cancer (OR=1.47) and seriousness of breast cancer (OR=1.28) were predictors of BSE practice after twelve months. The results provide evidence for the effectiveness an educational strategies using a multicomponent approaches in improving breast self-examination practice, knowledge of breast cancer and BSE and beliefs within young female students in Malaysia. This study suggests that the three interventions had impacts on knowledge, beliefs and BSE practice but there were no significant differences among them which should lead to recommendation that policy makers should adopt the cheapest and most feasible of the three intervention strategies.